Hello English Application in Teaching Grammar For Students at SMP Tri Dharma Palembang - Oktaverani, Dwi Andrea; Angraini, Nike; Permana, Dio Resta (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
In today's era, all learning processes use modern methods. Learning media could be easily found by utilizing the digital era like today. One of them is the Hello English application that can be used as learning media for students. Many students felt bored learning grammar, especially using books. Therefore, the research aimed to determine the grammar understanding using the Hello English application. This research used a pre-experimental method. The population in this study were eighth-grade students at SMP Tri Dharma Palembang. The 25 out of 51 students were selected as the sample. This research used a paired sample t-test, and validity, and reliability results were calculated with a Likert scale and Cronbach alpha. Before analyzing the data, the normality test was conducted. The results of the paired sample t-test in the experimental group showed that the pre-test and post-test of the experimental group obtained a t-value of 10.719 and a p of 0.01 (p < 0.05). This proves that there was any significant enhancement in understanding grammar using the Hello English application. The findings show that teaching grammar using the Hello English application enhanced students' understanding of the grammar of the simple present tense for eighth-grade students of SMP Tri Dharma Palembang in the academic year 2024/2025.I